Participative management of water resources under conditions of water scarcity in a semiarid region - Peixoto, Filipe da Silva; Silveira, Renata Câmara Miranda Nayara; Trinta, Michael Mitchell Araújo (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2017)
The adoption of the river basin as an unit of planning and management inserts, in a model of participative management of water resources, the River Basins Committees (RBC) as public spaces of consultative and deliberative nature making it increasingly necessary to develop this management model and to adapt it to regional realities. The studied RBC is located in a semiarid region, where the scarce water conditions are subject to periods of up to 5 years with rainfall amounts below normal. Thus, this study aimed to research the guidelines and decisions taken by the Curu River Basin Committee between the years 2009 and 2015. The guidelines and decisions were analyzed by an analytical matrix that lists them by typologies in order to assess their demands. This study produced subsidies for understanding the reality of the RBC actions, showing that is important to applied adaptations for RBC in semiarid regions due the constant drought.